Fattah, Irfan Abdul Hamid. “Contemporary Religious Thought and the Challenges of Modernity,” Year 7, Issue 26 (Fall 1422 AH/ 2001 CE), Pp. 17-41. - فتاح, عرفان عبد الحميد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2001)
Irfan Fattah’s article addresses the concept of modernity and its rise, citing positivist philosophy and the research methodologies that emerged from its intellectual space. It discusses European enlightenment philosophies, extremist human inclinations, materialist/atheist dialectic philosophy, and Darwin's theory of organic evolution and its implications in the field of the humanities in general. The article also addresses comprehensive secularization and the methodologies of modern historical/literary criticism of written texts solidified by revelation. Fattah discusses general responses of religious thought to the challenges of the era of modernity or the era of “post-religion,” addressing liberal Christian denominations, Jewish reformists movement, advocates of enlightenment in Islam, conservative Judaism, and orthodox and neo-orthodox doctrines.